Implementasi Kegiatan Kemasyarakatan Lingkungan Sosial di Desa Pantai Labu Pekan - Cindy Cinthia; Annisa Vani Ramadhani; Anisa Putri Manik; Anismar Anismar; Adelia Rizki Utami; Lidya Sofiana; Nurhayani Nurhayani; Wahyuni Wahyuni (Journal on Education, 2023)
Community service activities aim to socialize the community in environmental management activities in the surrounding community. This study aims to implement social environmental community activities in Pantai Labu Pekan Village. The method in this study is a qualitative method with a descriptive approach. Data collection techniques in this study through observation and documentation. The results of this study indicate that the community is very enthusiastic about the activities carried out by researchers, seen when researchers carry out various activities such as socialization activities, tutoring, evening recitation, and mutual cooperation they are very supportive of these activities. Through this activity it is hoped that the community can support each other to protect the environment in order to create a good environment.